User adaptation and informal activities in a controlled urban green open space (case study Taman Jurong, Kabupaten Bekasi) - Hadi Jaya Putra; Adilson Bendito Barreto Savio; Bugis Batubara; Evania Fortuna Luke; Pramesty Dyah Wardhani; Reinalda Hikmal Ramadhan (Jurnal Arsitektur Lansekap, 2025)
Public spaces are vital for cities, providing places for social, cultural, and economic activities. Green Open Spaces (GOS), like Taman Jurong in Jababeka, Bekasi, are especially important for promoting ecological balance, community interactions, and environmental sustainability. Taman Jurong combines greenery, recreational areas, and mobility functions, serving as a corridor and a community space. However, informal economic activities, such as street vending, and limited infrastructure have created challenges, disrupting its planned functions. Recent policies aim to enforce Taman Jurong’s role as an ecological and ventilation zone, prioritizing safety due to underground gas pipelines. These measures have reduced informal activities, ensuring environmental sustainability and minimizing safety risks. However, they have also decreased the park’s vibrancy and limited its appeal as a community space. Visitors now spend less time in the park, and vendors struggle to adapt, highlighting tensions between planned uses and informal needs. Despite restrictions, Taman Jurong remains valuable for its shady trees and cool environment, which continue to attract visitors. The study underscores the importance of balancing ecological preservation, safety, and community engagement to create inclusive and functional urban spaces. Taman Jurong illustrates how well-managed GOS can enhance urban life while meeting diverse needs.